Surgical Treatment of Abdominal Aortic Aneurysm Accompanied by Bilateral Large Multicystic Kidneys - Morita, Nobuyo; Kurose, Kimihiro; Kobata, Takashi; Matsubara, Junichi; Hida, Kenji; Suzuki, Kouji; Moriyama, Manabu; Shikata, Hiroo; Sakamoto, Shigeru (Japanese Journal of Cardiovascular Surgery, 2006)
Abdominal aortic aneurysm and cystic kidneys are both common diseases that have been increasingly detected due to the development of medical screening instruments, such as computed tomography and ultrasonography. We occasionally intraoperatively encounter abdominal aortic aneurysms accompanying cystic renal lesions. However, there have been extremely few reports about abdominal aortic aneurysms complicated by cystic renal disease. Large renal cysts or polycystic kidneys are at risk of rupture or intraoperative hemorrhage, and can hinder the surgical treatment of abdominal aortic aneurysm. Therefore, there is a significant need for surgeons to be able to preoperatively determine the potential of an interruption of the procedure, for example, due to a cystic lesion. In this paper, we report a case of a 77-year-old man with abdominal aortic aneurysm who complained of abdominal fullness due to the presence of large cystic lesions in both kidneys. Preoperatively we aspirated 1, 550ml percutaneously from bilateral renal cysts under ultrasonographic guidance, but did not instill sclerosing agents, such as ethanol. Three days after the percutaneous aspiration, surgical treatment of the abdominal aortic aneurysm (5.2cm in diameter), the left common iliac arterial aneurysm and the right common iliac arterial aneurysm (3.0 and 2.6cm in diameter) was performed through a median abdominal incision with a retroperitoneal approach. The arterial prosthesis used was a Y-shaped woven double velour vascular graft. The postoperative course was uneventful and the patient was discharged 14 days after the vascular reconstruction procedure. Our experience suggests that percutaneous aspiration of large renal cysts that might hinder the surgical procedure for abdominal aortic aneurysm is useful.